Soldagem dissimilar dos aços AISI 8630M e ASTM A182 F22 para aplicações subaquáticas - Oliveira, George Luiz Gomes de (2013)
The aim of this study was to evaluate the effect of welding technique in the AISI 8630M and ASTM A182 F22 steels applied in offshore structural components for Oil and Natural Gas sectors. Joints of AISI 8630M or ASTM A182 F22 were fabricated and previously buttered with nickel alloy Inconel 625 ® or an alloy of low carbon steel commonly used in welding of AISI 8630M. Different techniques of buttering were performed with and without post welding heat treatment (PWHT). For some of the joints buttered without PWHT, buttering layers were deposited in accordance with the welding parameters suggested by Higuchi and modified Higuchi tests previously performed. Mechanical tests (hardness, microhardness and fracture) were accomplished for buttering interfaces and an intense microstructural characterization (optical microscopy, scanning electron microscopy, EDS and EBSD) was realized. Higuchi test has been showed as a good option to select parameters for AISI 8630M and ASTM A182 F22 buttering. The joints that were buttered using the conditions indicated by Higuchi test showed an intense grain refinement in the HAZ of low alloy steels, while the ones that was buttered with the conditions disapproved showed a coarse granulation. The dissimilar interface showed off intermediate chemical composition between the steel and nickel alloy, and this interface was called high dilution zone (HDZ). The HDZ revealed points of high hardness and, even in samples subjected to PWHT was not possible to anneal these regions. The heat affected zone (HAZ) of the samples buttered using the parameters indicated by Higuchi (without PWHT) showed hardness values similar to those of the samples welded with parameters that failed in the Higuchi test and with PWHT. In general, fracture tests showed that the PWHT not bring significant toughness’s benefits to the HAZ, furthermore, may impair the toughness of dissimilar interface. The analysis of the preferred path for cracks propagation showed that the use of PWHT tends to weak the dissimilar interface, possibly this effect is related to carbon diffusion and possible carbide precipitation during this treatment. It is believed that this precipitation can be even more critical when considering a constant supply of hydrogen to the board (as in a cathodic protection), this reinforces the use of buttering techniques without subsequent heat treatment in the manufacture of this type of joints.